1997
DOI: 10.1080/095530097143167
|View full text |Cite
|
Sign up to set email alerts
|

A charged-particle microbeam: II. A single-particle micro-collimation and detection system.

Abstract: The use of a charged-particle microbeam provides a unique opportunity to control precisely, the number of particles traversing individual cells and the localization of dose within the cell. The accuracy of 'aiming' and of delivering a precise number of particles crucially depends on the design and implementation of the collimation and detection system. This report describes the methods available for collimating and detecting energetic particles in the context of a radiobiological microbeam. The arrangement dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The Gray Cancer Institute charged particle microbeam system was used for targeted irradiation [ 27 , 28 ]. Cells were seeded in the centre of Mylar foil dishes pretreated with 1.7 µg/cm 2 BD Cell-Tak adhesive (Becton Dickinson, Erembodegem, Belgium) and stained in medium containing a 0.8 µM concentration of the fluorescent dye Hoechst 33342 (Molecular Probes, Leiden, the Netherlands) to enable visualisation of cell nuclei by fluorescent microscopy at the microbeam stage.…”
Section: Methodsmentioning
confidence: 99%
“…The Gray Cancer Institute charged particle microbeam system was used for targeted irradiation [ 27 , 28 ]. Cells were seeded in the centre of Mylar foil dishes pretreated with 1.7 µg/cm 2 BD Cell-Tak adhesive (Becton Dickinson, Erembodegem, Belgium) and stained in medium containing a 0.8 µM concentration of the fluorescent dye Hoechst 33342 (Molecular Probes, Leiden, the Netherlands) to enable visualisation of cell nuclei by fluorescent microscopy at the microbeam stage.…”
Section: Methodsmentioning
confidence: 99%
“…The Gray Cancer Institute charged-particle microbeam facility was used for this study. Details of the experimental setup for nuclear targeting using the microbeam have been described previously (31, 32). Nonconfluent cells were seeded in a 6 × 6-mm area of a specially designed Mylar-based microbeam dish preincubated overnight with cell culture media.…”
Section: Methodsmentioning
confidence: 99%
“…Roeske and Stinchcomb (1996) have demonstrated that z 0 can be calculated from D 0 . Recent experimental advances allow for z 0 to be measured directly (Folkard et al 1997, Hei et al 1997, Pugliese et al 1997, Soyland et al 2000, Prise et al 2002, Wang et al 2003. These experiments use either track-etch techniques with computerized processing (Soyland et al 2000, Wang et al 2003 or microbeams (Folkard et al 1997, Hei et al 1997, Pugliese et al 1997, Prise et al 2002 to determine z 0 .…”
Section: Discussionmentioning
confidence: 99%